RURAL CUSTOMERS OPINION ABOUT THE USE OF ELETRONIC BANKING SERVICES WITH SPECIAL REFERENCE TO NAGAPATTINAM DISTRICT- AN EMPIRICAL STUDY - Balasubramanian, P.; Kalidoss, K. (International Journal of Psychosocial Rehabilitation, 2020)
The primary objective of this study was to assess the rural customers’ opinion about use of E-banking services. E-banking has been penetrated in the rural area as well and with the advanced availability of infrastructure the services have been spread to the geography. But still owing to non-internet connectivity or poor internet connectivity, though bankers are ready to provide the e-services it cannot be availed. Therefore, the descriptive research method was used. To assess the opinion of rural customers both qualitative and quantitative data were collected and used. Both primary and secondary data were collected from sample banks and customers. The multistage random sampling technique was used to select the sample banks and sample respondents in the study area. The population of the study was treated as unknown due to bank officials are not given the list of customers. Thus, the total of 384 rural customers was determined as sample size of the study by using Cohran sample size determination formula for unknown population. The analysis result reveals that the sample public sector customers have good opinion about to use of e-banking services in many ways i.e., irrespective of banks majority of the educated, salaried and business and profession occupation customers have the knowledge about e-banking services and use more and majority of the sample customers have stated that the computer self efficacy, cost charged by banks, role of safety, 24 hours service, role of privacy, role of bank officials and neighbours and friends have influenced lot to use of e-banking services than social influence and advertisement. On the other side, majority of the customers have stated that security is the biggest question while using e-banking services.